Critical review of flexible pavement maintenance management systems - A. Khalifa, Nasradeen .; Zulkiple, Adnan; Gheit Ali Alfughi, Abdalkrim; Ali Almukhtar attboli, Isa; Salem Abolbaida Ghammeid, Abbas (International Journal of Engineering and Technology, 2019)
Worldwide, the national road has a very important role to sustain and to increase the regionâ€™s economy, while its maintenance plays an essential and integral part in the life of road pavement. The road pavement maintenance management system (PMMS) is a systematic method for inspection and rating the pavement condition which ensure a timely maintenance solving altogether all undetected pavement defects. Defects in pavement is an issue of multiple dimensions which is due to the unforeseen increase of axle loading of commercial vehicles, the ad-hoc rapid expansion of the road network, the non-availability of up to date technology and equipment, poor quality of construction material, unavailability of skilled labor and lack of adequate funding provision. Essential road pavement maintenance is a set of activities directed towards keeping it in a serviceable state during its design life involving a variety of operational procedures such as identification of deficiencies, programming and scheduling for actual implementation in the field. Thus, the essential objective should be to keep the road surface and appurtenances in good condition and to extend the life of the road assets to its design life. Broadly, the activities include identification of defects and the possible cause there off, determination of appropriate remedial measures; and implementation these in the field inclusive of monitoring of the results. It is hope that the conclusion from this study will allow relevant authorities to employ a state-of-the-arts road maintenance system that is compatible to Highway Development and Management (HDM-4) analysis.Â Â